Brexit Poker – Wer hat die besseren Karten in den Austrittsverhandlungen? - Hans-Bernd Schäfer; Arkadiusz Radwan (Wirtschaftsdienst, 2016)
Die politische, wirtschaftliche und rechtliche Lage Großbritanniens gegenüber der Europäischen Union nach dem EU-Mitgliedschaftsreferendum und im Vorfeld der Austrittsverhandlungen stellt sich ungewiss dar. Die Autoren fassen die verfassungsrechtliche Kontroverse über die Kompetenz- und Verfahrensfragen zur rechtmäßigen Brexit-Durchführung zusammen. Darüber hinaus geben sie einen Überblick, inwiefern der Vertrag über die Europäische Union und der Vertrag über die Arbeitsweise der Europäischen Union die Entscheidungsfi ndung der Verhandlungspartner determinieren. Vermutlich wird Großbritannien, um den Zugang zum europäischen Markt nicht zu verlieren und um seine Rolle als Finanzzentrum sowie als Tor zu Europa für private Investoren aus Drittländern weiter spielen zu können, Transferleistungen an die EU akzeptieren und wesentliche Bereiche des Acquis Communautaire beachten müssen. – – The political, economic and legal situation of Great Britain vis-à-vis European Union in the aftermath of the membership referendum and awaiting the commencement of withdrawal negotiations is interesting. The authors summarise the legal controversy in the UK over the powers and procedures needed to be complied with in order to duly trigger the Brexit. They then sketch the legal framework as provided by the Treaty on European Union and the Treaty on the Functioning of the European Union to reconstruct the decision-making architecture under which parties to the upcoming negotiations will have to make their choices. After outlining the opportunity cost for Great Britain associated with leaving the Union, in particular those regarding the fi nancial institutions and foreign direct investments, they conclude that decision-making architecture governing the upcoming withdrawal negotiations puts Brussels in pole position vis-à-vis London. It is likely that Britain will have to accept transfer payments to the EU similar to, if not higher than the net transfers that have been due so far. Some degree of the compliance with the acquis communautaire, at least with regard to the treaty's fundamental freedoms (goods, workers, services, establishment and capital) will most likely also be expected from London, if it wants to benefit from access to the European market after the termination of its EU membership.
Keywords: F13; F15; K33; 330